STRATEGI PENGEMBANGAN WISATA DI PULAU SEMUJUR KABUPATEN BANGKA TENGAH - Pendi, Pendi; Kurniawan, Kurniawan; Muftiadi, Muhammad Rizza (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2024)
The uniqueness of Semujur Island tourism can be used as a forum for regional economic development that involves the roleof human resources and sustainable concepts. The aim of this research is to analyze appropriate strategies for developingtourism on Semujur Island. This research was carried out in November 2023 on Semujur Island, Central Bangka Regency.The method used is a descriptive survey with data obtained from primary data and secondary data, then a SWOT analysis iscarried out. The research results show that the priority strategy for tourism development on Semujur Island, Central BangkaRegency according to Iadran III (Self Improvement Strategy) is 1) Develop village regulations to emphasize the domicile ofresidents living on the island so that tourism awareness groups (pokdarwis) can be formed as the first step in developmentSemujur Island tour. 2) Carry out community empowerment for local residents to increase interest and awareness indeveloping tourism potential which can become a business opportunity in the economy. 3) Carry out repairs to neglectedpublic facilities and carry out regular maintenance and upkeep of these facilities by paying fees to visitors or the localcommunity.